Job Design of the Kleder in Cattle Distribution Chain on the Camara Nusantara Cattle Ship - Zulhijariyanto - Zulhijariyanto; Asnath Maria Fuah; Lucia - Cyrilla; Yunus - Triyonggo (Program Pascasarjana Universitas Sriwijaya, 2019)
The purpose of this study was to analyze and design the design of the kleder work on cattle transportation in the Camara Nusantara Livestock Ship. This study uses descriptive qualitative analysis method by conducting observations, documentation, literature studies, and direct interviews with the objects studied in the field. Primary data is obtained from the main actors and secondary data through observation, documentation, and literature. The work design was designed following the Mader-Clark approach and the cattle distribution chain was presented in the form of a flow chart. Based on the results of this study indicate that the kleder in the Camara Nusantara Livestock Ship does not yet have a design work and has not applied the job description and specifications of the work needed. This is indicated by the absence of work competency standards which are used as work guidelines so that the team does not carry out duties in accordance with their duties and authority on the Camara Nusantara Livestock Ship. Cow distribution chain that uses transportation The Camara Nusantara cattle ship has three distribution models. The most efficient distribution model is through breeders, cattle fattening companies, slaughterhouses, and consumers.